Brand Image Influence on UNIMED Students Purchasing Decisions During Boycott - Mica Siar Meiriza; Rey Septanislaus Togatorop; Maysri Handayani Putri Sinaga; Nazwa Aulia Putri; Krisdamaiyanti Hia (SYNERGY: Jurnal Bisnis dan Manajemen, 2025)
This study examines the influence of brand image on consumer purchasing decisions at McDonald's during the boycott period caused by the Israeli-Palestinian conflict. The boycott movement reflects a combination of cultural, ethical, and religious considerations influencing consumer behavior. The research focused on Medan State University students, utilizing a quantitative approach with a survey method. Data were collected from 100 respondents through an online questionnaire and analyzed using simple linear regression. The findings reveal that brand image significantly and positively impacts purchasing decisions, accounting for 61.2% of the variance. Despite the boycott, McDonald's strong brand image helped sustain consumer loyalty, emphasizing the importance of brand perception in mitigating external pressures. However, regional variations and other factors such as peer influence and personal ethics also play a role in shaping consumer behavior. This study highlights the resilience of brand image during socio-political crises but also exposes the limitations of boycott campaigns targeting well-established global brands. The results underscore the need for culturally specific strategies by activists and proactive crisis management by corporations. Future research should explore additional variables influencing consumer decisions to provide a more comprehensive understanding of these dynamics